2015
DOI: 10.1007/s10661-015-4627-y
|View full text |Cite
|
Sign up to set email alerts
|

Presence of aflatoxin M1 in raw, reconstituted, and powdered milk samples collected in Algeria

Abstract: Aflatoxins are potent toxic metabolites produced by Aspergillus spp. Aflatoxin M1 (AFM1) is a metabolite of aflatoxin B1 that can be present in milk, and it is a public health concern. There is scarce information on the incidence of aflatoxin M1 contamination in milk consumed in Algeria. The presence of AFM1 was investigated in raw milk samples collected between February and October 2011 from 11 dairy farms representative of Algerian production conditions and that were located around Constantine city. Reconsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…To the best of our knowledge, only one study on milk contamination by AFM 1 in Algeria has been published, concerning the city of Constantine (in the northeast of the country) [37]. In the study, AFM 1 was detected in 5 (11%) out of 47 samples, at levels ranging from 9 to 103 ng/L, with one sample exceeding the limit of 0.050 µg/kg set by the EU.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…To the best of our knowledge, only one study on milk contamination by AFM 1 in Algeria has been published, concerning the city of Constantine (in the northeast of the country) [37]. In the study, AFM 1 was detected in 5 (11%) out of 47 samples, at levels ranging from 9 to 103 ng/L, with one sample exceeding the limit of 0.050 µg/kg set by the EU.…”
Section: Discussionmentioning
confidence: 89%
“…Unfortunately, the maximum permissible level of AFM 1 in milk has not been established in Algeria. To the best of our knowledge, only one preliminary study of AFM 1 milk contamination has been performed, and in only one district, in Algeria [37].…”
Section: Introductionmentioning
confidence: 99%
“…e high percentage of contaminated samples with AFM1 in the current study could be due to the use of contaminated batches of milk powder or contaminated raw milk for producing these samples. Many authors have observed a higher prevalence of contamination with AFM1 in liquid milk (89%), of which 7.4% exceeds the threshold set by European regulations [29]. Similarly, in Iran, studies have evaluated the level of AFM1 in reconstituted milk and reported the presence of AFM1 in milk.…”
Section: Liquid Milk Samplesmentioning
confidence: 99%
“…Por otra parte, en Argelia, debido a la poca información sobre la contaminación de leche por AFM1, Redouane-Salah et al (43) investigaron su presencia en muestras de leche cruda, leche en polvo y leche reconstituida. Detectaron que el 11% del total de las muestras estaban contaminadas a niveles de 0,001 µg/L y entre 0,009 -0,103 µg/L para leche cruda y en polvo, respectivamente.…”
Section: Aflatoxina M1 En Leche De Vacaunclassified